Monitoring pharmaceuticals photo-Fenton degradation process by using Solid Phase Extraction and liquid chromatography - Melo, Silene A. S. [UNESP]; Bautitz, Ivonete R. [UNESP]; Pupo Nogueira, Raquel F. [UNESP] (Taylor & Francis Inc, 2008)
The recovery of the pharmaceuticals bezafibrate and tetracycline from water was evaluated, using Solid Phase Extraction (SPE) with the aim of applying this technique to interrupt the pharmaceuticals' photodegradation by photo-Fenton process for further analysis. Sep-Pack C-18, Strata X, and Oasis HLB cartridges were evaluated. Oasis HLB showed the most satisfactory recovery and repeatability results: 98% (CV - 1%) for bezafibrate (20.0 mg L-1) and 76% (CV = 1%) for tetracycline (25.0 mg L-1). There was not a significant decrease in recovery at lower concentrations of the pharmaceuticals, and neither when present in Sewage Treatment Plant (STP) effluent matrix.
Keywords: advanced oxidation process; bezafibrate; sewage treatment plant; solid phase extraction; tetracycline